Theory of constraint application on quality management and organizational performance in the construction industry - Hemaloshinee, Vasudevan A. (INTI International University, 2021)
This paper aims to review the relationship between the construction industry and the theory of constraints, which significantly impact quality management and organizational performance. Several studies have shown that adopting and implementing quality management is likely to improve an organization's performance. As a result, the relationship between quality management and organizational performance in the construction industry has not been extensively researched by linking this theory (e.g. theory of constraint). This review paper contributes to the body of knowledge on quality management and organizational performance by linking the theory of constraints to improve performance in the Malaysian construction industry through empirical evidence. Practically, this paper gives construction industry practitioners a push to better understand the roles of quality management and its ability to improve organizational performance through its theory of constraint (TOC) use. This review recommended that the analysis of structures should continue by using long-term activity-based costing (ABC) tools in future research.